Giorgos Vavouranakis, Konstantinos Kopanias and Chrysanthos Kanellopoulos (eds). Popular Religion and Ritual in Prehistoric and Ancient Greece and the Eastern Mediterranean. pp. xviii + 170, with col. and b/w ills. 2018. Oxford: Archaeopress. - Papantoniou, Giorgos (Journal of Greek Archaeology, 2020)
Popular religion falls under the wider field of popular culture, and has only recently been recognised as an independent subject for historical investigation. This volume concerns popular religion and ritual in prehistoric and ancient Greece and the eastern Mediterranean, and is the result of a conference held in December 2012 at the National Kapodistrian University of Athens.